2010
DOI: 10.1146/annurev-clinpsy-090209-151437
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Women's Mental Health: The Impact of Physical, Sexual, and Psychological Aggression

Abstract: The reach of violence against women (VAW) has been profoundly felt by women across the United States and around the globe. VAW has been documented for decades as a legal and social justice problem, but as illuminated in this review, it is also a substantial mental health concern. A full understanding of the phenomenon must include discussion of how often it occurs, in what forms, and to whom. This review defines violence against women in its variant forms and examines the literature on the mental health effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
147
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(173 citation statements)
references
References 103 publications
12
147
0
8
Order By: Relevance
“…Data from the National Intimate Partner and Sexual Violence Survey find that nearly 1 in 2 women and 1 in 5 men have experienced sexual violence other than rape, while 1 in 5 women and 1 in 71 men have experienced rape in their lifetime (Black et al, 2011). Survivors of sexual violence face serious mental health consequences including PTSD, depression, anxiety, and substance abuse (Jordan, Campbell, & Follingstad, 2010).…”
Section: Abstract: Trauma; Evidence-based Practice; Ptsd; Rape; Rape mentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the National Intimate Partner and Sexual Violence Survey find that nearly 1 in 2 women and 1 in 5 men have experienced sexual violence other than rape, while 1 in 5 women and 1 in 71 men have experienced rape in their lifetime (Black et al, 2011). Survivors of sexual violence face serious mental health consequences including PTSD, depression, anxiety, and substance abuse (Jordan, Campbell, & Follingstad, 2010).…”
Section: Abstract: Trauma; Evidence-based Practice; Ptsd; Rape; Rape mentioning
confidence: 99%
“…Systematic reviews of the adverse effects of childhood sexual abuse and sexual assault in adulthood reveal a broad constellation of psychological, behavioral, social, and physical health difficulties that negatively impact the lives of survivors (Bohn & Holz, 1996;Campbell, Dworkin, & Cabral, 2009;Jordan et al, 2010). PTSD, depression, anxiety, and substance abuse are among the most frequently reported mental health consequences and are often co-occurring (Chen & Ullman, 2010;Jordan et al, 2010;Kilpatrick, Resnick, Ruggiero, Conoscenti, & McCauley, 2007;Walsh, Galea, & Koenen, 2012). Voth Schrag and Edmond (2015) found that for RCC counselors reducing symptoms of anxiety, depression, and PTSD were among the most frequently endorsed treatment goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPV has a severe impact on victims particularly in relation to their physical (e.g., cuts, bruises, broken bones), mental (e.g., PTSD, depression) and health (e.g., chronic pain syndrome, cardiovascular disease) wellbeing (Jordan et al, 2010).…”
Section: Extent Of Intimate Partner Violencementioning
confidence: 99%
“…The accessibility and availability of counseling services is essential for victims to manage the psychological impact both in the period immediately following victimization and in the long term (Campbell, 2008;Martin & Parcesepe, 2013). Literature supports the importance of post assault mental health services (Campbell, 2008;Jina & Thomas, 2013;Jordan, Campbell, & Follingstad, 2010;Kumar, Nizame, & Srivastava, 2013;Mason & Lodrick, 2013;Patterson, Greeson, & Campbell, 2009). The findings from this current study revealed the importance of having an adequate number of mental health service providers available who can rapidly arrange counseling for a woman who is experiencing an acute need for mental health care.…”
Section: Perceived Sociocultural Expectationsmentioning
confidence: 99%